Phenotypic and molecular differences among rhizobia that nodulate Phaseolus lunatus in the Supe valley in Peru - Matsubara, M (2015)
A collection of 16 bacterial strains isolated from root nodules of Lima bean (Phaseolus lunatus L.) in the Supe valley of Peru were characterised using phenotypic and molecular methods. The isolates were clustered into fastgrowing, alkalinising and extra-alkalinising slow-growing isolates with marked morphological differences, according to the rate of growth and alkalinisation of yeast extract mannitol (YEM) medium. Fast-growing isolates were salt tolerant and sensitive to 40 °C, while alkalinising slow-growing isolates behaved oppositely. Extra-alkalinising slow-growing isolates were sensitive to 8 °C and 40 °C and tolerated 1 % NaCl. Fastgrowing isolates also showed higher indole-3-acetic acid (IAA) production and tri-calcium phosphate solubilisation than the alkalinising slow-growing isolates. Half of the isolates were able to nodulate Phaseolus vulgaris and Vigna unguiculata. Individually, BOX-PCR, ERIC-PCR, and REPPCR fingerprints patterns resulted in ten profiles from 16 isolates and they were clustered into three profile groups that correspond to the clusters obtained by YEM medium alkalinisation. Analysis of 16S rRNA gene sequences revealed that fast-growing isolates showed 99.7 % sequence identity with Rhizobium mesosinicum CCBAU 25010T and Rhizobium alamii GBV016T . Alkalinising slow-growing isolates were related to both Bradyrhizobium yuanmingense CCBAU10071T and Bradyrhizobium liaoningense 2281T , with 99.8 % sequence identity, and extra-alkalinising slowgrowing isolates had 100 % sequence identity to both Bradyrhizobium paxllaeri LMTR 21T and Bradyrhizobium icense LMTR 13T.